Menggali Nilai-Nilai Filosofis dalam Ungkapan Masyarakat Hitu untuk Pemberdayaan Sosial dan Budaya - Tabelessy, Novita; Somelok, Grace (Universitas Pattimura, 2025)
This Community Service activity aims to explore the philosophical values contained in the traditional expressions of the Hitu community in Central Maluku as a basis for social and cultural empowerment. Expressions such as “Baku timba, baku tolong” (We are one, we help each other), “Ale rasa, beta rasa” (You feel, I feel), and “Beta pung negeri, ale pung negeri, sama-sama jaga” (My country, your country, let's protect it together) reflect ethical principles such as solidarity, empathy, collective responsibility, and love for the land of the ancestors. Through a qualitative approach and contextual analysis, this study shows that these expressions are not only cultural heritage, but also have great potential as instruments of social development rooted in local identity. The results of this study emphasize the importance of preserving and actualizing local wisdom values in strengthening cultural resilience and forming an inclusive, empowered, and characterful society.